1989
DOI: 10.1177/014272378900900607
|View full text |Cite
|
Sign up to set email alerts
|

Prespeech and early speech development of two late talkers

Abstract: Speech samples of 34 children were analysed to determine patterns of babbling and early word productions from 9 to 24 months. The present study focuses on the vocal and verbal development of two 'late talkers' in the group who did not meet the criterion for achieving the Meaningful Speech Stage until 24 months. Analysis of these subjects' prespeech utterances revealed that one of them produced few canonical babbles from 9 to 21 months; the other displayed an unusual pattern of sound preference in his babbles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
186
0
4

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(202 citation statements)
references
References 9 publications
12
186
0
4
Order By: Relevance
“…This result is not surprising in light of the prevalence of delayed reduplicated babble in the group and the fact that delayed babble has been shown to relate to delayed language (e.g., Oller, Eilers, Neal, & Schwartz, 1999;Stoel-Gammon, 1989). It is also very much in line with other recent studies of Infant Siblings in the second and third years that have reported delays in language using both standardized and parent report measures (Mitchell et al, 2006;Yirmiya et al, 2006a;Yirmiya et al, 2006b;Zwaigenbaum et al, 2005).…”
Section: Group Patterns Of Delaysupporting
confidence: 84%
See 2 more Smart Citations
“…This result is not surprising in light of the prevalence of delayed reduplicated babble in the group and the fact that delayed babble has been shown to relate to delayed language (e.g., Oller, Eilers, Neal, & Schwartz, 1999;Stoel-Gammon, 1989). It is also very much in line with other recent studies of Infant Siblings in the second and third years that have reported delays in language using both standardized and parent report measures (Mitchell et al, 2006;Yirmiya et al, 2006a;Yirmiya et al, 2006b;Zwaigenbaum et al, 2005).…”
Section: Group Patterns Of Delaysupporting
confidence: 84%
“…While this may sound like a task for the specialist, Oller and colleagues (Oller, Eilers, Neal, & Cobo-Lewis, 1998;Oller et al, 1999) have demonstrated that if interviewed appropriately, caregivers can be remarkably accurate reporters of babble onset and production by their infants. This may be a useful procedure to incorporate into surveillance visits for very young Infant Siblings, as the absence of babble by 10 months is considered to be a moderately sensitive index of risk for later language delay and developmental disorder (Oller et al, 1998(Oller et al, , 1999Stoel-Gammon, 1989). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental tracking of these features by automated means at massive scales could add a major new component to language acquisition research. Given their infrastructural character, anomalies in development of rhythmic/syllabic articulation and voice might also suggest an emergent disorder (17,18).…”
mentioning
confidence: 99%
“…It has often been hypothesized that the first speech-like articulation and the babbling phase, which occur at approximately 10 months of age, allow infants to develop a link between articulatory settings and the resulting auditory consequences, thus laying down the basis for the development of the phonetic inventory and adaptation to the ambient language (Westermann and Miranda, 2004). Several longitudinal studies, conducted on different populations and using different modes of analysis, indicated a continuity between prelinguistic production (babbling) and first words both in typically developing children (Bates, Benigni, Bretherton, Camaioni and Volterra, 1979;Leonard and Bortolini, 1998;Locke, 1989;Oller, Eilers, Neal and Schwartz, 1999;Vihman and McCune, 1994) and in children with language delay (D'Odorico, Bortolini, De Gasperi and Assanelli, 1999;Oller, Eilers, Neal and Cobo-Lewis, 1998;Rescorla, Dahlsgaard and Roberts, 2000;Stoel-Gammon, 1989).…”
mentioning
confidence: 99%